A Randomized Controlled Trial of Concentrated ERP, Self-Help and Waiting List for Obsessive- Compulsive Disorder: The Bergen 4-Day Treatment - Launes, Gunvor; Hagen, Kristen; Sunde, Tor; Öst, Lars-Göran; Klovning, Ingrid; Laukvik, Inger-Lill; Himle, Joseph A.; Solem, Stian; Hystad, Sigurd W.; Hansen, Bjarne; Kvale, Gerd (Frontiers in Psychology, 2019)
Background The Bergen 4-day treatment (B4DT) is a concentrated exposure-based treatment for patients with Obsessive-Compulsive Disorder (OCD) delivered during four consecutive days. The B4DT has in a number of effectiveness studies demonstrated promising results as approximately 90% of patients gain reliable clinical change post-treatment and nearly 70% are recovered on a long-term basis. Methods The current study is the first randomized controlled trial evaluating the effects of the B4DT. Forty-eight patients diagnosed with OCD were randomized to B4DT, self-help (SH), or waiting list (WL) with 16 patients in each condition. All participants randomized to the B4DT underwent the treatment without any attrition. Results The B4DT yielded significantly better effects than control conditions on measures of OCD, depression, and generalized anxiety. The response rate (≥35% reduction of the individual patient’s pre-treatment Y-BOCS score) was 93.8% in B4DT, 12.5% in SH and 0% in WL, while remission rate (response criterion is fulfilled and the post-treatment Y-BOCS score is ≤12 points) was 62.5%, 6.3%, and 0%, respectively. Furthermore, patients who had received the B4DT, showed improved work- and social functioning. None of the patients treated with B4DT showed signs of deterioration. In comparison, one patient in the SH condition was in remission, and one showed significant clinical improvement, whereas the remaining showed no change. Conclusion The results indicate that the B4DT is an effective treatment for patients suffering from OCD. Clinical Trial Registration www.ClinicalTrials.gov, identifier NCT02886780.